Does argon anoxia cause a color change in Prussian blue pigment?. Issue 1 (3rd April 2018) - Koestler, Daniel; Ballard, Mary W.; Charola, A. Elena; Koestler, Robert J.
ABSTRACT: The study focused on the effect of anoxic treatment on the discoloration of Prussian blue-dyed textiles and paper. Prussian blue pigment has been known to change color in the presence of light and heat in a vacuum for quite some time, but some claims were made that a low-oxygen environment alone contributed to its fading. The aim of this study was to determine whether argon anoxic treatment would induce the same changes when kept in the dark or in the light. The results clearly show that fading of Prussian blue in an argon anoxic condition occurs in the light but not in the dark.